(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2016)
We obtain the differential equations of loxodromes on canal surfaces which cut all meridians or parallels at a constant angle in the Euclidean 3-space. Also we compute the arc-lengths of loxodromes and give some examples by using Mathematica to illustrate our results.